Comparação do desempenho de indivíduos normo-ouvintes no teste de índice de reconhecimento de fala à viva voz regional e fala gravada paranaense em diferentes cidades do Brasil - Mafra, Nicoli Valverde (2015)
Introduction: the investigation of the perception of speech is currently a topic widely discussed. The speech tests, such as speech audiometry , are important in the audiological diagnosis, measuring the ability to perceive and recognize the verbal sounds. One of speech audiometry tests most commonly used in clinical practice is Speech Recognition Index, performed with the method speakerphone and the recorded speech in standard CD player . The open outcry method can be influenced before the intra- and interfalante variability and linguistic regionalism, on the other hand recorded speech tests provide consistency of their presentation. In Brazil, the test made the speakerphone has been routine in most clinics and audiology clinics. However, the literature argues that the recorded and standardized material allows the reliability of data collection. Goal: his study aimed to analyze the results before the test application, two methods: the speakerphone and recorded speech Paraná , in different populations of Brazil. Method: the sample consisted of 125 subjects, 25 each region (Rio de Janeiro , Florianópolis , Porto Alegre , Salvador and Curitiba ), of both sexes aged 20 to 70 years, applying the test in both methods of analysis, being recorded material Paraná. Results: the findings showed prevalence percentage in hit improvement in CD method recorded in all regions , with better answers for Rio de Janeiro (40%), Salvador, Porto Alegre e Florianópolis (28%). Conclusion: it was concluded that the influence of regional aspects of the recording, he had no significance in view of the improvement in the use of recorded material Paraná in cities like southeast. It suggests that the use of recorded material to be included in clinical routine and that further research related to the method used for speech tests are specified and published